Effectual SVPWM Techniques and Implementation of FPGA Based Induction Motor Drive - Saravanan M; Nandakumar R; Veerabalaji G (Institute of Advanced Engineering and Science, 2012)
This paper presents a field programmable gate array(FPGA)-based control integrated circuits(IC) for controlling the pulsewidth modulation (PWM) inverter used in power conditioning system for ac-voltage regulation. Space vector pulsewidth modulation(SVPWM) algorithm offers great flexibility to optimise switching waveform. Among them,double edge triggering can be implemented, It consumes less power compare to other PWM techniques. The SVPWM pulses thus generated through Xilinx is given as switching pulses to voltage source inverter(VSI) circuit to trigger the motor. The delay time of PWM output is programmable and SVPWM control IC is reprogrammable.It shows the advantage of lower total harmonic distortion(THD) without increasing the switching losses. Results are provided along with simulation analysis in terms of THD,output fundamental voltage and voltage transfer ratio to verify the feasibility of operation. The SVPWM switching pattern has been achieved with a fundamental frequency of 50HZ.